The feasibility of a systems-based approach in non-profit strategic planning, monitoring and evaluation: development and asssessment of the SAMEL toolkit - Horler, Jessica (School of Management Studies, 2025)
Recent trends in programme evaluation highlight increasing interest in using systems thinking to enhance the relevance and suitability of evaluation in complex social settings. However, the literature reveals a significant gap in practice-oriented empirical research on applying systems thinking to monitoring, evaluation, and learning (MEL) in non-profit organisations (NPOs). This research addresses this gap by testing the feasibility of a systems approach to MEL development in NPO settings. Employing a multi-phase exploratory design, developed the Systems Approach to MEL (SAMEL) Toolkit for evaluators to aid NPOs in developing MEL frameworks through structured, facilitated workshops. The Toolkit was first reviewed by experts and adjusted accordingly. It was then tested with two early childhood development NPOs, with workshops facilitated by myself and another evaluator. Data were collected using workshop observations, focus group discussions, interviews with the evaluator, facilitation journals, and follow-up interviews with NPO directors and the other evaluator. The data were analysed using reflexive thematic analysis. Key findings suggest systems thinking can significantly enhance strategic planning and MEL readiness in NPOs through its application to programme theory. However, MEL implementation faces substantial challenges due to contextual and organisational complexities, particularly with regard to funding. While systems thinking enhances NPO teams' strategic clarity and critical appraisal of programme design, NPOs have limited ability and capacity to act on these insights. An accountability culture and results-based management orientation to funding significantly constrains the flexibility demanded by systems thinking approaches. Based on these findings, this thesis recommends exploring ways to enhance the suitability of systems thinking for NPOs, including capacity-building and changes to rigid funding and reporting requirements.